PENGARUH FRAKSI VOLUME SERAT TERHADAP KEKUATAN GESER KOMPOSIT BERPENGUAT SERAT IJUK (Acak-Anyam-Acak) DENGAN RESIN POLYESTER - Mochamad Arif Irfa’i (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
The many vehicle components often found as a result of their failure to receive the shear loads. The purpose of this study was to determine the effect of fiber volume fraction to the shear strength of composite reinforced sugar palm fiber (random, woven, random) with a polyester resin. Fiber volume fraction (Vf) used was in this study was 35%, 45%, 50%, 55% and 60%. The method of manufacture composite done hand lay up with a laminate consisting of random sugar palm fiber, woven sugar palm fiber and random sugar palm fiber. Dimensions of test specimens and shear testing procedures refers to the ASTM D-1037 standard. Shear testing performed three times for each test group. Macro photo performed after a shear test. Macro photo made on a fracture cross section shear test to determine the pattern of failures in the composite. The results showed that the shear strength of the composite increases with increasing fiber volume fraction. Increased shear strength was greatest in fiber volume fraction (Vf) = 45% which amounted to 9466.45 MPa, while the lowest shear strength occurred in fiber volume fraction (Vf) = 60% which amounted to 7118.67 MPa. Identification of fracture cross section shows that the pattern of failure was generally dominated by the release of the bond between the fibers with the matrix (delamination) followed by a fracture or fiber break.